2019
DOI: 10.1016/j.proci.2018.06.147
|View full text |Cite
|
Sign up to set email alerts
|

Flame macrostructures and thermoacoustic instabilities in stratified swirling flames

Abstract: The present article investigates the correlation between flame macrostructures and thermoacoustic combustion instabilities in stratified swirling flames. Experiments are carried out in a laboratory scale longitudinal test rig equipped with the Beihang Axial Swirler Independently-Stratified (BASIS) burner, a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 40 publications
2
27
0
Order By: Relevance
“…Recently, the fact that the flame primarily responds to hydrodynamic disturbances (originally excited by the acoustics) has been exploited by using incompressible LES (Febrer et al, 2011;: the convective flow speed rather than the speed of sound then determines the time step and thus allows much larger values, making incompressible simulations significantly faster than fully compressible ones. With this approach, a complete FDF for a premixed bluff-body stabilised flame was accurately predicted , as were the nonlinear FDFs of a swirling premixed flame and a very long non-swirling flame (Xia, Li, et al, 2017;Li et al, 2017) and, recently, the linear flame response of a stratified flame (Han et al, 2018), etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the fact that the flame primarily responds to hydrodynamic disturbances (originally excited by the acoustics) has been exploited by using incompressible LES (Febrer et al, 2011;: the convective flow speed rather than the speed of sound then determines the time step and thus allows much larger values, making incompressible simulations significantly faster than fully compressible ones. With this approach, a complete FDF for a premixed bluff-body stabilised flame was accurately predicted , as were the nonlinear FDFs of a swirling premixed flame and a very long non-swirling flame (Xia, Li, et al, 2017;Li et al, 2017) and, recently, the linear flame response of a stratified flame (Han et al, 2018), etc.…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, a novel burner (BASIS) designed at Beihang University [13,24] is used to study the aero-thermodynamic behaviour and combustion instabilities of LPP combustors. Its detailed geometry is sketched in CSL stands for the central shear layer originating from the pilot stage, while ISL and OSL stand for the inner and outer shear layer of the main stage, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…But the both combustors in Refs [6,12] feature complicated geometries and were not shown in detail. Recently, a simplified stratified burner was developed by the authors' group [13] to elucidate the role of the pilot flame in anchoring the main flame experimentally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During experiments, they observed three different flame modes depending on the equivalence ratio. They demonstrated that lifted and V-type flames are more prone to flame instabilities [4].…”
Section: Introductionmentioning
confidence: 99%